2022
DOI: 10.1002/cam4.5391
|View full text |Cite
|
Sign up to set email alerts
|

Costimulatory molecule‐related lncRNA model as a potential prognostic biomarker in non‐small cell lung cancer

Abstract: Objective: Costimulatory molecules have been demonstrated to exert essential roles in multiple cancers. However, their role in lung cancer remains elusive.Here, we sought to identify costimulatory molecule-related lncRNAs in nonsmall cell lung cancer (NSCLC) and establish a prognostic signature to predict the prognosis of patients with NSCLC.Methods: A total of 535 lung adenocarcinoma (LUAD) and 502 lung squamous cell carcinoma (LUSC) patients from the cancer genome atlas (TCGA) database were recruited. A nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…Studies have reported that the enrolled 8 TNF-related lncRNAs (LINC01137, LINC02310, AC017100.1, AC108676.1, AC118757.1, AL357873.1, AC104971.3, and HLA-DQB1-AS1) are closely related with cancer progression. LINC01137 has been shown to play an oncogenic role in NSCLC and oral squamous cell carcinoma, which is similar with our results that NSCLC patients with low expression of LINC01137 were likely to exhibit better outcomes ( 32 , 33 ). Zhao et al .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Studies have reported that the enrolled 8 TNF-related lncRNAs (LINC01137, LINC02310, AC017100.1, AC108676.1, AC118757.1, AL357873.1, AC104971.3, and HLA-DQB1-AS1) are closely related with cancer progression. LINC01137 has been shown to play an oncogenic role in NSCLC and oral squamous cell carcinoma, which is similar with our results that NSCLC patients with low expression of LINC01137 were likely to exhibit better outcomes ( 32 , 33 ). Zhao et al .…”
Section: Discussionsupporting
confidence: 92%
“…These TNF-related lncRNAs were involved in carcinogenesis, and inflammatory and immune responses ( 22 - 25 ). A number of studies have also demonstrated that some of TNF-related lncRNAs are closely associated with cancer proliferation and survival ( 32 - 38 ). Thus, we analyzed the expression patterns and clinical significance of TNF-related lncRNAs in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…The secreted lncRNAs act as a messenger and can be packed in extracellular vesicles including exosomes. Recently, the exosomal lncRNAs in patients with cancers had provided both diagnostic and prognostic clues for the management of their malignancies [ 20 , 25 ]. We demonstrated different expression levels of 5 lncRNAs, which have been thought to have oncogenic or tumor suppressor roles in various cancers in the exosomes, ANCT, and tumor tissues of patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…The gene coding lncRNA-GHSROS is antisense located on the ghrelin receptor encoding a 1.1 kb transcript [ 26 ]. It has been reported that lncRNA-GHSROS is expressed in prostate and breast cancers, and its overexpression is correlated with advanced tumor stages [ 25 , 27 ]. Overexpression of this lncRNA results in increased cellular proliferation and vascularization of tumor tissues [ 27 ].…”
Section: Discussionmentioning
confidence: 99%